2003
DOI: 10.1046/j.1440-1738.2003.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ pressure–temperature conditions of a tectonic mélange: Constraints from fluid inclusion analysis of syn‐mélange veins

Abstract: Pressure and temperature (P–T) conditions of mélange formation are estimated from fluid inclusions within “syn‐mélange” veins developed in the necks of boudins of sandstone blocks in the mélange of the Shimanto accretionary complex, south‐west Japan. The mélange records décollement‐zone processes. P–T conditions are in the range of 81 (+15) to 235 (±18) MPa and 150 (±25) to 220 (±31)°C. Assuming a constant fluid‐pressure to lithostatic‐pressure ratio for each data set, we estimate a P–T gradient of between 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…This result suggests that the H 2 O‐CH 4 immiscible fluids might have coexisted at the time of vein precipitation. In the case of immiscible fluid, homogenization temperature is directly regarded as fluid trap temperature [ Alderton and Bevins , 1996; Lewis et al , 2000; Hashimoto et al , 2002, 2003; Matsumura et al , 2003]. Assuming that the modes observed on frequency histograms of homogenization temperatures represent the original homogenization temperatures and fluids were H 2 O‐CH 4 immiscible fluid, the temperatures of precipitation of the network and fault‐fill veins are therefore estimated to be ∼150–160°C and ∼160–170°C, respectively.…”
Section: Syn‐tectonic Mineral Veins In the Mugi Mélangementioning
confidence: 99%
“…This result suggests that the H 2 O‐CH 4 immiscible fluids might have coexisted at the time of vein precipitation. In the case of immiscible fluid, homogenization temperature is directly regarded as fluid trap temperature [ Alderton and Bevins , 1996; Lewis et al , 2000; Hashimoto et al , 2002, 2003; Matsumura et al , 2003]. Assuming that the modes observed on frequency histograms of homogenization temperatures represent the original homogenization temperatures and fluids were H 2 O‐CH 4 immiscible fluid, the temperatures of precipitation of the network and fault‐fill veins are therefore estimated to be ∼150–160°C and ∼160–170°C, respectively.…”
Section: Syn‐tectonic Mineral Veins In the Mugi Mélangementioning
confidence: 99%
“…Vrolijk et al . 1988; Sakaguchi 1999; Hashimoto et al . 2002, 2003; Lewis & Byrne 2003; Matsumura et al .…”
Section: Introductionunclassified
“…Geological studies of on-land tectonic mélange have shown that sandstones are finely broken [e.g., Cowan, 1982;Byrne, 1984;Agar, 1990]. Although the mechanical behavior of sandstone has been well studied by many experiments [e.g., Zhang et al, 1990aZhang et al, , 1990bMarone et al, 1990;Wong et al, 1997], quantitative evaluation of the deformation conditions are sparse, except for some inferences on the P-T conditions [Vrolijk, 1987;Hashimoto et al, 2002Hashimoto et al, , 2003Lewis and Byrne, 2003;Matsumura et al, 2003]. Constraining the deformation and lithification process of sandstone is therefore one of the keys to understanding the onset of the seismogenic zone.…”
Section: Introductionmentioning
confidence: 99%